Intermolecular FRET Pairs as An Approach to Visualize Specific Enzyme Activity in Model Biomembranes and Living Cells - Igor D. Zlotnikov; Alexander A. Ezhov; Elena V. Kudryashova (Biophysica)
Herein, we propose an analytical approach based on intermolecular fluorescent resonant energy transfer (FRET) pairs for the visualization of specific enzyme activity in model biomembranes and in living cells. Cell visualizations with fluorescent confocal laser microscopy usually rely on fluorescent probes, such as Fluorescein isothiocyanate (FITC), Alexa488, Tetramethylrhodamine isothiocyanate (TRITC) and many others. However, for more specific tasks, such as the detection of certain enzymatic activity inside the living cell, the toolbox is quite limited. In the case of enzyme-hydrolases for example, the choice is limited to organic molecules comprising a fluorescent dye (typically, 4-methylumbelliferone (MUmb) or 7-amino-4-methylcoumarin (AMC) derivatives) and a fluorescence quencher, bound via an enzyme-sensitive linker—so that when the linker is degraded, the fluorescent signal increases. Unfortunately, both MUmb and AMC are quenched and have a relatively low quantum yield in cells, and their excitation and emission ranges overlap with that of intracellular fluorophores, often producing a strong background noise. R6G, on the other hand, has excellent quantum yield apart from intracellular fluorophores, but there are no efficient quenchers that could be chemically linked to R6G. Herein, we show that R6G is able to form intermolecular FRET pairs with MUmb or AMC, with the latter serving as fluorescence donors. This yields a combination of R6G’s excellent fluorescence properties with a possibility to use an enzyme-sensitive linker in MUTMAC or AMC derivatives. This phenomenon was initially discovered in a model system, reversed micelles, where the donor, the acceptor, and the enzyme are forced to be in close proximity to each other, so that proximity could serve as an explanation for the intermolecular FRET effect. Surprisingly enough, the phenomenon has been reproduced in living cells. Moreover, we were able to create working intermolecular donor–acceptor FRET pairs for several different enzymes, including chymotrypsin, phosphatase, and asparaginase. This appears counterintuitive, as besides the overlap of the emission spectra of the donor and the absorption spectra of the acceptor, there are other criteria for the FRET effect, including the convergence of two fluorophores at a distance of about 1–10 nm, and the orientation of their dipoles at a certain angle, which is difficult to imagine in a bulk system like a living cell. We hypothesize that FRET-enabling donor–acceptor interaction may be taking place at the inner surface of the lipid bilayer, to which both donor and acceptor molecules would likely have an affinity. This hypothesis would require a more detailed investigation. Therefore, we have shown that the method suggested has good potential in the visualization of enzyme functioning inside living cells, which is often a challenging task. Shifting of the fluorescence signal to the long-wavelength region would increase the signal selectivity, making it easily distinguishable from autofluorescence.